PENINGKATAN KAPASITAS PENGELOLA RUMAH SINGGAH UNTUK ANAK JALANAN YAYASAN BINA ANAK PERTIWI - Ardista, Maria V.; Lithania, Maria; Hardi, Anastasia; Priya, Nikolas; Angela, Gabriela; Ajisuksmo, Clara R.P. (Jurnal Bakti Masyarakat Indonesia, 2020)
This activity is part of the final project of the Atma Jaya Faculty of Psychology Community Based Education course. In this activity students as a group conduct problems and needs assessments, and design and implement a communication capacity building program in the management of NGO organizations that provide assistance to street children. The student group consists of five people, carrying out activities at the Bina Anak Pertiwi Foundation (YBAP) an NGO that provides assistance to street children. There are two stages of activities carried out namely, the first stage is the assessment of problems and needs, and the second stage is the intervention to increase the capacity of YBAP management and staff. During the problem and needs assessment stage, interviews were conducted with four key informants and problem tree analysis. The results of the problem and needs assessment show that communication between management, staff, and foster children is the main problem faced by YBAP in carrying out the program of activities to assist street children. At the intervention stage, management capacity building is carried out with a focus on communication. Capacity building was carried out through four activity sessions, namely the first "Who Am I", which aims to increase their awareness of themselves as a companion to street children. The second session "They need Us" which aims to raise awareness about who and how the characteristics they serve and assist. The third session is "Chitty chatty" which aims to improve verbal and non-verbal communication skills, and the fourth session is "Broken square" which aims at increasing empathy skills and the importance of commitment to achieving common goals. The whole process of activities is carried out by participatory methods through group dynamics games, and at the end of the game there is a "debriefing" so that all participants get "insight" on the group dynamic games that are run. ABSTRAK: Kegiatan ini merupakan bagian tugas akhir dari mata kuliah Pendidikan Berbasis Komunitas Fakultas Psikologi Unika Atma Jaya. Dalam kegiatan ini mahasiswa secara berkelompok melakukan asesmen permasalahan dan kebutuhan, serta merancang dan melaksanakan program peningkatan kapasitas komunikasi dalam manajemen organisasi LSM yang memberi pendampingan kepada anak jalanan. Kelompok mahasiswa terdiri dari lima orang, melakukan kegiatan di Yayasan Bina Anak Pertiwi (YBAP) sebuah LSM yang memberikan pendampingan kepada anak jalanan. Ada dua tahap kegiatan yang dilakukan yaitu, tahap pertama asesmen permasalahan dan kebutuhan, serta tahap kedua intervensi peningkatan kapasitas pengurus dan staff YBAP. Pada tahap asesmen permasalahan dan kebutuhan, dilakukan wawancara dengan empat orang informan kunci dan analisis pohon masalah. Hasil asesmen permasalah dan kebutuhan menunjukkan bahwa komunikasi antara pengurus, staff dan anak binaan menjadi persoalan utama yang dihadapi oleh YBAP dalam melaksanakan program kegiatan pendampingan anak jalanan. Pada tahap intervensi, dilakukan peningkatan kapasitas manajemen dengan fokus pada komunikasi. Peningkatan kapasitas dilakukan melalui empat sesi kegiatan, yaitu pertama “Siapa Saya”, yang bertujuan untuk meningkatkan kesadaran mereka akan diri mereka sebagai pendamping anak jalanan. Sesi kedua “Mereka butuh Kita” yang bertujuan meningkatkan kesadaran mengenai siapa dan bagaimana karakteristik yang mereka layani dan dampingi. Sesi ketiga adalah “Chitty chatty” yang bertujuan meningkatkan keterampilan komunikasi verbal dan non verbal, dan sesi keempat adalah “Broken square” yang berujuan meningkatkan keterampilan berempati dan pentingnya komitmen untuk mencapai tujuan bersama. Seluruh proses kegiatan dilakukan dengan metode partisipatoris melalui permainan dinamika kelompok, dan di setiap akhir permainan dilakukan “debriefing” sehingga seluruh peserta memperoleh “insight” atas permainan dinamika kelompok yang dijalankan.